PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SISWA KELAS III SEKOLAH DASAR 01 HULU SUNGAI - Stefanus Ando; Tahmid Sabri; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the effect of using audio-visual media in Civic Educationlearning on student learning outcomes in class III State Elementary School 01 HuluSungai, the number of students is 20 people. The method used is a quasi-experimentaldesign with the type of Time-Series Design. The population in this proposal is all thirdgrade students of State Elementary School 01 Hulu Sungai. The research procedure willbe carried out in the 2nd semester of February-March 2020. The technique used is a test.The analytical technique used to calculate the mean is Mean= =∑ fi . xi∑ fi , standarddeviation using SD = √∑ D2−[(∑D2)/np]np−1, to calculate the effect size using ES = Ye− YcSe, withthe result that tcount is 3,716 and ttable is 2,093. Because tcount (3.716) > ttable (2.093), it issaid to be significant, so therefore Ha is accepted. So it can be said that there is an effectof using audio-visual media on the learning outcomes of civic education lessons for thirdgraders at the 01 Hulu Sungai State Elementary School. effect size results obtained resultsof 0.830 with the "medium" category.Keywords: Influence, Audio Visual Media, Citizenship Education